Knockdown of mediator subunit Med19 suppresses bladder cancer cell proliferation and migration by downregulating Wnt/β‐catenin signalling pathway. Issue 12 (19th June 2017) - Yuan, Hejia; Yu, Shengqiang; Cui, Yuanshan; Men, Changping; Yang, Diandong; Gao, Zhenli; Zhu, Zhe; Wu, Jitao
Abstract: Mediator complex subunit 19 (Med19), a RNA polymerase II‐embedded coactivator, is reported to be involved in bladder cancer (BCa) progression, but its functional contribution to this process is poorly understood. Here, we investigate the effects of Med19 on malignant behaviours of BCa, as well as to elucidate the possible mechanisms. Med19 expression in 15 BCa tissues was significantly higher than adjacent paired normal tissues using real‐time PCR and Western blot analysis. Immunohistochemical staining of 167 paraffin‐embedded BCa tissues was performed, and the results showed that high Med19 protein level was positively correlated with clinical stages and histopathological grade. Med19 was knocked down in BCa cells using short‐hairpin RNA. Functional assays showed that knocking‐down of Med19 can suppress cell proliferation and migration in T24, UM‐UC3 cells and 5637 in vitro, and inhibited BCa tumour growth in vivo . TOP/FOPflash reporter assay revealed that Med19 knockdown decreased the activity of Wnt/β‐catenin pathway, and the target genes of Wnt/β‐catenin pathway were down‐regulated, including Wnt2, β‐catenin, Cyclin‐D1 and MMP‐9. However, protein levels of Gsk3β and E‐cadherin were elevated. Our data suggest that Med19 expression correlates with aggressive characteristics of BCa and Med19 knockdown suppresses the proliferation and migration of BCa cells through down‐regulating the Wnt/β‐catenin pathway, thereby highlighting Med19 as a potential therapeutic target for BCa treatment.